Thirty-five years of political geography and Political Geography: The good, the bad and the ugly. (July 2018) - O'Loughlin, John
Abstract: When Political Geography (Quarterly) was established in 1981, the field barely registered in the international social science community and had become a "moribund backwater". The journal has motivated and reflected a sizable body of published works for almost two generations. The impact of these articles, however, is muted for a variety of reasons including a large diversity of subjects and methodologies, a lack of sustained and replicable research on important contemporary subjects, a tendency to dilettantism, and a failure to achieve any coherent notion of what constitutes political geographic research. Because the discipline of political geography is so amorphous and opaque to both its practitioners and observers, the potential benefits of its approach are muted and its achievements enervated. The field's achievements can partly be gauged by a comparison of the journal's content to its original agenda. Notable missed opportunities for focus and impact are identified, especially in a failure to clarify the important role that context plays in political behavior. Publication expectations in academia have changed, propelling authors to try to rush to print, while not coincidentally publishing production standards have slipped. The likely trends are further centrifugal pressures on disciplinary staples and an erosion of what seemed like a relatively coherent sub-discipline in 1981.